2015
DOI: 10.1186/s10194-015-0576-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of RAMP1 gene in migraine: an exploratory analysis

Abstract: BackgroundReceptor activity modifying protein 1(RAMP1) is a key receptor subunit of calcitonin gene related peptide (CGRP) playing a critical role in migraine. But variations in RAMP1 gene have not been found to link with migraine. Still it is elusive that DNA methylation at RAMP1 promoter is associated with migraine.MethodsA total of 51 blood DNA samples from 26 patients with migraine and 25 matched healthy controls were collected, extracted and treated with bisulfate. Subsequently DNA methylation levels at R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…It has been also shown that the glutamatergic system is involved in the pathophysiology of migraine [ 30 ]. DNA methylation status of RAMP1 gene has been shown to be associated with migraine [ 31 ]. Rs4379368 in the C7orf10 gene and rs13208321 in the FHL5 gene have been reported to be associated with migraine [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been also shown that the glutamatergic system is involved in the pathophysiology of migraine [ 30 ]. DNA methylation status of RAMP1 gene has been shown to be associated with migraine [ 31 ]. Rs4379368 in the C7orf10 gene and rs13208321 in the FHL5 gene have been reported to be associated with migraine [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when methylation levels in the latter region decreased below 3.50%, the risk of migraine increased significantly in women but not in men. Therefore, the authors suggest that methylation of this region in peripheral leukocytes could be considered an "epigenetic biomarker" to predict migraine risk in the female population [128]. Despite its limitations in terms of the limited number of samples and testing only in leukocytes, this study provides the first evidence that DNA methylation in the promoter region of the RAMP1 gene may play a role in migraine.…”
Section: Environmental Factors and Migrainementioning
confidence: 86%
“…Meanwhile the indirect involvement of regulation of CALCA and RAMP1 genes in migraine susceptibility has been suggested in several studies. Wan et al examined whether the methylation pattern in the promoter region of the RAMP1 gene in peripheral leukocytes is associated with migraine [128] by studying 51 subjects (26 patients with migraine and 25 healthy age-and gendermatched controls) who were treated with bisulfite followed by measurement of DNA methylation levels within the RAMP1 promoter region. Overall, no significant difference between migraine patients and controls was observed in the methylation of 13 CpG sites within the promoter region of the gene, specifically at base positions between -300 and 205 bases with respect to the start of transcription.…”
Section: Environmental Factors and Migrainementioning
confidence: 99%
“…However, the 3 studies found significant differences in DNA methylation between patients and controls at the SLC6A5 gene, 30 in proximity of the NPTX2 and SH2D5 genes, 83 and at the CGRP promoter region. 82 It is interesting to note that all the aforementioned genes are involved in regulating, respectively, neurotransmitter transport, neural activity, synaptic plasticity, and neural sensitisation. Taken together, these results suggest that migraine and headache are associated with hypomethylation in genes regulating neuronal functions.…”
Section: Research On Dna Methylationmentioning
confidence: 99%